Molecular characterization of a new virus species identified in yam (Dioscorea spp.) by high-throughput sequencing - Silva, G.; Bömer, M.; Rathnayake, A.I.; Sewe, S.O.; Visendi, P.; Oyekanmi, J.O.; Quain, M.D.; Akomeah, B.; Kumar, P. Lava; Seal, S.E. (MDPI, 2019)
To date, several viruses of different genera have been reported to infect yam (Dioscorea spp.). The full diversity of viruses infecting yam, however, remains to be explored. High-throughput sequencing (HTS) methods are increasingly being used in the discovery of new plant viral genomes. In this study, we employed HTS on yam to determine whether any undiscovered viruses were present that would restrict the international distribution of yam germplasm. We discovered a new virus sequence present in 31 yam samples tested and have tentatively named this virus “yam virus Y” (YVY). Twenty-three of the samples in which YVY was detected showed mosaic and chlorotic leaf symptoms, but Yam mosaic virus was also detected in these samples. Complete genome sequences of two YVY viral isolates were assembled and found to contain five open reading frames (ORFs). ORF1 encodes a large replication-associated protein, ORF2, ORF3 and ORF4 constitute the putative triple gene block proteins, and ORF5 encodes a putative coat protein. Considering the species demarcation criteria of the family Betaflexiviridae, YVY should be considered as a novel virus species in the family Betaflexiviridae. Further work is needed to understand the association of this new virus with any symptoms and yield loss and its implication on virus-free seed yam production.